Naber and toning in the modern Arab poetry Mahmoud Darwish, a model - Eathar Shukri Shaker al-Nuaimi; Arif Abdul Sayel Rishawi (College of Education for Women, 2019)
Naber and toning in the modern Arab poetry Mahmoud Darwish, a model